Sistem Informasi Pemetaan Hasil Integrasi Layanan Primer Poskesdes Sukodono Desa Sukodono Pacitan - Sinta Arum Pratiwi; Andi Setya Permana; Zaid Sholihul Qodri; Edy Susena (SIBER PRESS Universitas SIBERMU, 2024)
Primary health care is one of the pillars of health transformation that focuses on meeting health needs based on the life cycle that is easily accessible and affordable to the community, family and individual levels. Primary health care is also an important initial foundation in the health service system, which is usually carried out by encouraging increased promotive and preventive efforts, supported by innovation and utilization of technology. Like the Sukodono Pacitan Health Post which has an innovation by developing a mapping information system or GIS (Geographic Information System), namely combining Sukodono Health Post service data that can be used to view and evaluate health data better and more efficiently. The method used is a prototype, which is used to align customer discrepancies related to technical materials and specifications of expected needs on an ongoing basis. This system was created with the aim of helping and facilitating health post officers and Sukodono villagers for better health facilities.